Influence of anticoagulant therapy on immune and inflammatory response in patients with community-acquired pneumonia associated with coronavirus infection - Avhaitis, S. S.; Авгайтіс, С. С. (Запорізький державний медико-фармацевтичний університет, 2024)
Aim. To determine the effect of anticoagulant therapy on the immune and inflammatory response in patients with community- acquired pneumonia associated with coronavirus infection. Material and methods. An open, prospective, observational study was conducted in the period from January 2021 to February 2022 at the Kherson City Clinical Hospital named after Athanasius and Olga Tropin of the Kherson City Council, 143 patients with community-acquired pneumonia aged 46 to 65 years who tested positive for SARS-CoV-2 were observed. To participate in the study, patients signed a voluntary consent form. Results. Patients with community-acquired pneumonia develop an immune-inflammatory response characterized by increased levels of interleukin-6 and C-reactive protein, with significantly higher values of these biomarkers in combination with COVID-19. Combination therapy is effective in reducing the levels of markers of the immune-inflammatory response Heparin at a dose of 1000 IU/h is more effective in reducing the risk of death in patients with community-acquired pneumonia associated with coronavirus infection than 100 IU anti-Xa/kg (1 mg/kg) twice daily. Conclusions. The results of our study showed that therapy with heparin is more effective than enoxaparin in reducing interleukin-6 levels within 72 hours (by -12.93 % vs -4.75 %, respectively, p < 0.05). Multivariate regression analysis determined that changes in the levels of D-dimer, interleukin-6 and INR were independent predictors of adverse disease outcome. Мета роботи – визначити вплив терапії, що включала антикоагулянти, на показники імунозапальної відповіді у хворих на негоспітальну пневмонію, асоційовану з коронавірусною інфекцією. Матеріали і методи. Здійснили відкрите, проспективне, обсерваційне дослідження в період з січня 2021 до лютого 2022 року на базі КНП «Херсонська міська клінічна лікарня мені Афанасія і Ольги Тропіних» Херсонської міської ради. Під спостереженням перебували 143 хворих на негоспітальну пневмонію віком від 46 до 65 років, які мали позитивний тест до SARS-CoV-2. Для участі в дослідженні пацієнти підписали форму добровільної згоди на участь. Результати. У хворих на негоспітальну пневмонію спостерігали розвиток імунозапальної відповіді, що характеризувалася підвищенням рівнів інтерлейкіну-6 та С-реактивного білка. Значення цих біомаркерів достовірно вищі при поєднанні з COVID-19. Комбінована терапія є ефективною для зниження рівнів маркерів імунозапальної відповіді. Гепарин у дозі 1000 МО/год ефективніше знижує ризик смерті в пацієнтів із негоспітальною пневмонією, що асоційована з коронавірусною інфекцією, ніж 100 МО анти-Ха/кг (1 мг/кг) двічі на добу. Висновки. Результати дослідження показали: терапія, що включала гепарин, ефективніше порівняно з еноксапарином знижує рівні інтерлейкіну-6 протягом 72 годин (на -12,93 % vs -4,75 % відповідно, р < 0,05). Згідно з результатами мультиваріантного регресійного аналізу, незалежними предикторами несприятливого перебігу захворювання є зміни рівнів D-димеру, інтерлейкіну-6 і МНВ.
Вплив терапії, що включала антикоагулянти, на показники імунозапальної відповіді у хворих на негоспітальну пневмонію, асоційовану з коронавірусною інфекцією
Keywords: immune response; pneumonia; COVID-19; anticoagulant therapy; heparin; enoxaparin; interleukin-6; C-reactive protein; імунозапальна відповідь; негоспітальна пневмонія; антикоагулянтна терапія; гепарин; еноксапарин; інтерлейкін-6; С-реактивний білок